Perceptual Advantage of Animal Facial Attractiveness: Evidence From b-CFS and Binocular Rivalry - Shang, Junchen; Liu, Zhihui; Yang, Hong; Wang, Chengyu; Zheng, Lingya; Chen, Wenfeng; Liu, Chang Hong (Frontiers in Psychology, 2020)
Research has shown that attractive human faces enjoy an advantage in both conscious and preconscious processing. Here we examined whether this preference for attractiveness is exclusive to human faces by measuring participants’ sensitivity to the attractiveness of cat and tiger faces. Experiment 1 measured the time taken to break continuous flash suppression (b-CFS), whereas Experiment 2 measured the dominant time in binocular rivalry (BR). The results showed that attractive cat faces were detected more quickly (Experiment 1) and dominated for longer time in visual awareness (Experiment 2). However, no effect of attractiveness was found for tiger faces in Experiment 1, while attractive tiger faces also dominated for longer time in visual awareness in Experiment 2. The results provide first evidence that the preference for attractive animal faces can be shown involuntarily or without apparent conscious control. The findings suggest that human preference for facial attractiveness may contain an aesthetic element rather than being a purely adaptive means for mate choice.